Effect of cypermethrin on the growth and development of the jute hairy caterpillar, Spilarctia obliqua (Walker) - Khan, AR; Saha, BN (University Journal of Zoology, Rajshahi University, 2007)
Key words: Spilarctia obliqua; cypermethrin; growth; development Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 93-97